Standardized uptake value (SUV) as semi-quantitative analysis of myocardial perfusion study - Kaalam, Sabturia (2020)
This study aimed to investigate the ability of SUV measurement in analyzing the myocardial perfusion finding by comparing the SUV mean and SUV max with the qualitative imaging finding. Applying SUV as semi-quantitative analysis might ease the analyzation process of the image finding due to the probability of inconsistencies finding from the visual evaluation which is the current method used in interpreting the SPECT/CT images. In this study, a sample of two patients from the Nuclear Medicine Imaging Department of Hospital Universiti Sains Malaysia was retrospectively taken. The SUV mean SUV max and uptake of the tracer in each of the left ventricle walls were derived using the GE Myovation Evolution® and GE Q.Metrix software. Every region of the four walls (anterior, lateral, inferior, and septa wall) of the left ventricle were drawn manually and the measurement of the SUVs and uptake was recorded based on the drawn region. A p-value < 0.05 indicates that it is statistically significant. As a result, there were no significant differences between SUV mean and SUV max with the uptake from each of the left ventricle wall with a p-value of 0.602 (p>0.05). There was a strong linear relationship found between both SUV mean and SUV max with age, weight, and height of the samples with r=0.873, p<0.05, and r=0.768, p<0.05 respectively. In conclusion, there is a bright chance of implementing SUV as a semi-quantitative analysis in myocardial perfusion imaging finding in the future.